The glass spare - DeStefano, Lauren (Glass Spare, 2017)
After discovering that she has the ability to turn people into gemstones, Wilhemina, the fourth daughter of the wealthiest nation's king, seeks redemption putting herself in the path of a cursed prince who has his own ideas about Wil's power.